South African Renal Registry Annual Report 2018 - Davids, M Razeen; Jardine, Thabiet; Marais, Nicola; Jacobs, Julian C; Sebastian, Sajith (African Journal of Nephrology, 2020)
The seventh annual report of the South African Renal Registry summarises the 2018 data on kidney replacement therapy (KRT) for patients with kidney failure in South Africa. In December 2018, the number of patients who were being treated with chronic dialysis or transplantation stood at 10 730, a prevalence of 186 per million population (pmp). Most patients are treated with haemodialysis in the private healthcare sector, where the prevalence was 839 pmp. In the public sector, which serves 85% of the South African population, the prevalence of KRT (67 pmp) remained below the level reported for 1994. Limpopo and Mpumalanga remain the most under-served provinces and Blacks the most under-served population group. The Western Cape province had the highest public sector treatment rates by a large margin and was also where most of the country’s public sector kidney transplants were performed.